The role of cognitive competence in sustaining competitive advantage: Analytical Research of the Views of Sample of the Directors of the Islamic University of Najaf - Abdullah Amanah, Ahmed; Hamid Ismail Mohsen, Amjad; Wadi Jaz Al-Jubouri, Haitham (Iraqi Journal for Administrative Sciences, 2024)
This research aims to determine the role of cognitive competence in sustaining competitive advantage in our Iraqi organizations. The dimensions of cognitive competence (information technology, decision-making, creative thinking) have been adopted. As well as adopting the dimensions of the competitive advantage (low cost, quality, flexibility, delivery). As the Islamic University in Najaf was chosen as a field for research, through a questionnaire that included (34) members of the university administration. The questionnaire was adopted as a main tool for obtaining research data, which was prepared by reference to the ideas of a number of researchers according to ready-made standards. The data were analyzed using the ready-made statistical program (SPSS V.25), (Smart PLS V.20), and among the most important tools used in the analysis are: the weighted arithmetic mean, standard deviation, Pearson correlation coefficient, and simple linear regression. And one of the most prominent conclusions that were reached was that cognitive competence in its dimensions has an active and positive role in enhancing competitive advantage and its sustainability. Accordingly, the researchers recommended the necessity of increasing the university administration’s interest in the research community in studying aspects of the benefit of cognitive competence and employing its dimensions in the sustainability of its competitive advantage to face the various challenges that private education organizations face.